Employee Generated Content (EGC) By the Owner of Shaera Coffee on Tiktok - Ane Septiani; Aghnia Dian Lestari (CV. Media Digital Publikasi Indonesia, 2026)
TikTok is one of the platforms that encourages companies to utilize digital content as part of their marketing strategy. One effective approach is Employee Generated Content (EGC), which is content created voluntarily by internal employees. EGC content is considered more authentic and trustworthy by the audience. Shaera Coffee is a culinary business that uses TikTok through the @ininabizu account by posting content created directly by its owner as an example of EGC. This study aims to evaluate how the interaction, authenticity, originality, and credibility of the content created by the owner of Shaera Coffee on TikTok @ininabizu contributes to building trust with the audience. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The research shows that the owner's direct involvement in creating content results in active interaction, authentic content, and a higher level of credibility in the eyes of the audience. Therefore, EGC plays an important role in building trust and a sustainable relationship between Shaera Coffee and its TikTok audience.